Measles transmission by 'fly‐in fly‐out' workers in Australia. (5th September 2013) - Burgess, Christopher P.; Markey, Peter; Skov, Steven; Dowse, Gary
Abstract Objective: To describe the outbreak investigation and control measures for a cluster of measles cases involving 'fly‐in fly‐out' (FIFO) workers on an off‐shore industrial vessel. Methods: Following Australian guidelines, measles cases were interviewed and at‐risk contacts on the Australian mainland received measles vaccine, immunoglobulin or health advice. For the industrial vessel: (i) exposed FIFO workers who had already left the vessel received health advice through their employer; (ii) workers remaining on the vessel were offered measles vaccine; and (iii) FIFO workers joining the vessel for 21 days following the prodrome onset of the last case of measles on the vessel were offered measles vaccine. Measles virus isolates were sent for genotype determination. Results: Four measles cases from two Australian jurisdictions were epidemiologically linked to the retrospectively identified index case, a New Zealand FIFO worker. No further cases were detected following the institution of outbreak control measures. Conclusion: FIFO workers congregating on large industrial projects are a discrete risk group with the potential to spread infectious diseases over large distances, both domestically and internationally. Implications: FIFO workers' immunisation history should be reviewed prior to deployment. Catch‐up vaccination, where appropriate, would minimise transmission of vaccine‐preventable diseases such as measles and help maintain a healthy, productive workforce.